2021
DOI: 10.7150/jca.62112
|View full text |Cite
|
Sign up to set email alerts
|

Linc01513 inhibits the malignant potential of Nasopharyngeal carcinoma by binding to PTBP1

Abstract: LncRNAs are reported to be involved in tumor proliferation, invasion and metastasis, and are considered as potential biomarkers and therapeutic targets for human cancer, including head and neck cancer. In this study, we screened the differentially low-expressed linc01513 by bioinformatic to detect its expression and biological effect on nasopharyngeal carcinoma (NPC). MTT was used to evaluate the effect of linc01513 on the proliferation of NPC cells. Wound healing assay was used to determine the cells migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We found that GDPD4-2, AC144450.1, LINC01513, AC004009.2, AL096869.1, AP005210.1, and BX119924.1 were significantly underexpressed in PCa. LINC01513 was underexpressed in nasopharyngeal carcinoma ( Wang J. et al, 2021 ). However, AC144450.1 has been found to be highly expressed in the breast tissue relative to the adjacent tissue ( Hassani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that GDPD4-2, AC144450.1, LINC01513, AC004009.2, AL096869.1, AP005210.1, and BX119924.1 were significantly underexpressed in PCa. LINC01513 was underexpressed in nasopharyngeal carcinoma ( Wang J. et al, 2021 ). However, AC144450.1 has been found to be highly expressed in the breast tissue relative to the adjacent tissue ( Hassani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%